ANALISIS IMPLEMENTASI PROGRAM BEASISWA CREDIT UNION KELING KUMANG PADA ANGGOTA TINGKAT SMA - Tusti, Sablan; Salim, Izhar; Fatmawati, Fatmawati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study entitled " Analysis the Implementation of  Keling Kumang Credit Union Scholarship Program at Senior High School. The main problem of this research was the implementation of the Keling Kumang Credit Union Scholarship Program at Senior High School. The aim of this study was to know the forms, activities and results of the implementation of Keling Kumang Credit Union scholarship program for high school.The method of this research was descriptive and using qualitative approach.The tools of data collection were done by observation, interview, and documentation. The source of data used the primary data and the secondary data. Processing and data analysis technique were done through three stages, that were reduction data,presentation data, and conclusion. The results of this study indicate that (1) the implementation of  Keling Kumang Credit Union scholarship program to the members were educational assistance and supply the product saving and loan in order to make it easier for members to prepare for the next education (2)the activities carried out by administrators at senior high school members were  socialization and training,the purpose of this these activities were to gain knowledge and experience (3) the result of the implementation of scholarship program for senior high school  members was the various activities that held by the Keling Kumang Credit Union can be seen through the number of members both the amount of deposits and the number of loans, and the number of members who received the scholarship.  Keywords: Implementation, Scholarship, The Members of Credit Union.